Sejarah, Ilmu Pengetahuan, dan Sosiologi Pendidikan Islam - Ikbal, Muhammad; Idi, Abdullah; Karoma, Karoma; Fikri, Aiman (Universitas Batanghari Jambi, 2025)
This paper discusses the crucial role of sociology in Islamic education, focusing on the history, goals, andscope of Islamic educational sociology. In Indonesia, educational sociology is essential for understanding andaddressing educational challenges, such as regional disparities, low literacy rates, and rapid social changes. Thispaper also examines the contributions of sociology as a science in identifying social factors that influence educationand developing solutions for a more inclusive and adaptive educational system. Using a sociological approachgrounded in Islamic values, this study seeks to connect Islamic education with evolving social dynamics. The study’sfindings indicate that the application of educational sociology can act as a solution to enhance the quality ofeducation in alignment with the needs of society and the workforce in Indonesia.